Reciprocal regulation of the Autophosphorylation of Enzyme I(Ntr) by Glutamine and α-Ketoglutarate in Escherichia coli - Lee, Chang-Ro (2013)
In addition to the phosphoenolpyruvate:sugar phosphotransferase system (sugar PTS), most proteobacteria possess a paralogous system (nitrogen phosphotransferase system, PTS(Ntr)). The first proteins in both pathways are enzymes (enzyme I(sugar) and enzyme I(Ntr)) that can be autophosphorylated by phosphoenolpyruvate. The most striking difference between enzyme I(sugar) and enzyme I(Ntr) is the presence of a GAF domain at the N-terminus of enzyme I(Ntr). Since the PTS(Ntr) was identified in 1995, it has been implicated in a variety of cellular processes in many proteobacteria and many of these regulations have been shown to be dependent on the phosphorylation state of PTS(Ntr) components. However, there has been little evidence that any component of this so-called PTS(Ntr) is directly involved in nitrogen metabolism. Moreover, a signal regulating the phosphorylation state of the PTS(Ntr) had not been uncovered. Here, we demonstrate that glutamine and α-ketoglutarate, the canonical signals of nitrogen availability, reciprocally regulate the phosphorylation state of the PTS(Ntr) by direct effects on enzyme I(Ntr) autophosphorylation and the GAF signal transduction domain is necessary for the regulation of enzyme I(Ntr) activity by the two signal molecules. Taken together, our results suggest that the PTS(Ntr) senses nitrogen availability.